Neutralizing Perceptions of BPR Hard Part among Shipyard Employees - Ismail, Azman; Hasni Osman, Nor (International Journal of Engineering and Technology, 2018)
Deploying of BPR faces a lot of challenges either during pre-implementation, post-implementation,or both. Negative perceptions of BPR are one of the challenges normally happened during BPR deployment andit must be neutralized before it creates unnecessary resistance among employees. This research aims toneutralized BPR hard part such as radical change, clean slate process, and top down approach during revampingof project disbursement process in Shipyard. This study used qualitative method with interactive ActionResearch Cycle to neutralized BPR hard part using available BPR key critical success factors within Shipyardworking environment. The findings were based on interview conducted on twelve interviewees from Shipyardâ€™scross-functional department and stake holders related to project disbursement process. Negative perceptionduring pre-implementation was gradually reduced and become more positive after applying BPR key CSFâ€™sduring project implementation.Â Â